1994
DOI: 10.1515/zna-1994-1-255
|View full text |Cite
|
Sign up to set email alerts
|

43Ca NMR Study of Bismuth-Based High-Tc Superconductors

Abstract: As a first step of a study of the electronic properties of C u 0 2 planes by probing calcium nuclei in the bismuth-based high-Tc materials we report here the structural assignment of Ca N M R lines measured in 43Ca-enriched samples of n = 2 ((Bi,Pb)2Sr2CaCu2O g+x) and n = 3 ((Bi,Pb)2Sr2-Ca2C u 3O 10+Jl.) bismuth compounds. Powdered samples were investigated as well as oriented pow ders, achieved by uniaxial alignment of the grains in a 7T magnetic field. For the main calcium site (Ca between two C u 0 2 planes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The magnetogyric ratio is fairly low, thereby also contributing to difficulties in observing this nucleus (γ = −1.803 × 10 7 rad T −1 s −1 ; ν 0 = 33.66 MHz at 11.75 T). For these reasons, the literature is not extensive for this nucleus although recent natural abundance work by Smith and co-workers as well as some studies on isotopically enriched slags and glasses, along with the increasing availability of very high field SSNMR spectrometers, has rekindled interest in 43 Ca. A particularly outstanding example reported this year by Laurencin et al demonstrated the utility of triple-quantum 43 Ca magic-angle spinning (MAS) NMR in distinguishing between the two crystallographically distinct calcium sites in hydroxyapatite. , This work also impressively showed that natural abundance 43 Ca− 1 H rotational-echo double-resonance (REDOR) experiments are feasible, thereby opening the door to distance measurements involving calcium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetogyric ratio is fairly low, thereby also contributing to difficulties in observing this nucleus (γ = −1.803 × 10 7 rad T −1 s −1 ; ν 0 = 33.66 MHz at 11.75 T). For these reasons, the literature is not extensive for this nucleus although recent natural abundance work by Smith and co-workers as well as some studies on isotopically enriched slags and glasses, along with the increasing availability of very high field SSNMR spectrometers, has rekindled interest in 43 Ca. A particularly outstanding example reported this year by Laurencin et al demonstrated the utility of triple-quantum 43 Ca magic-angle spinning (MAS) NMR in distinguishing between the two crystallographically distinct calcium sites in hydroxyapatite. , This work also impressively showed that natural abundance 43 Ca− 1 H rotational-echo double-resonance (REDOR) experiments are feasible, thereby opening the door to distance measurements involving calcium.…”
Section: Introductionmentioning
confidence: 99%
“…7 The magnetogyric ratio is fairly low, thereby also contributing to difficulties in observing this nucleus (γ ) -1.803 × 10 7 rad T -1 s -1 ; ν 0 ) 33.66 MHz at 11.75 T). For these reasons, the literature is not extensive for this nucleus [8][9][10][11][12][13][14][15][16][17][18][19][20] although recent natural abundance work by Smith and co-workers [21][22][23] as well as some studies on isotopically enriched slags and glasses, [24][25][26][27] along with the increasing availability of very high field SSNMR spectrometers, has rekindled interest in 43 Ca. A particularly outstanding example reported this year by Laurencin et al demonstrated the utility of triple-quantum T h i s c o n t e n t i s o n l y l i c e n s e d f o r c o n s u m between the two crystallographically distinct calcium sites in hydroxyapatite.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, 17 O, 27 Al, and 43 Ca have large quadrupole moments, resulting in broad resonances with irregular lineshapes. Furthermore, 17 O and 43 Ca have very low natural abundances, further reducing the ease of data collection. Studies of 17 O, 57 Fe, and 43 Ca suffer further still from the nuclei's exceptionally low magnetogyric ratios, the latter two especially so. As a consequence of these factors, the two main thrusts of the field focus on either 27 Al or 29 Si NMR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Here H (1) Q is the ® rst-order quadrupolar Hamiltonian, e 2 qQ / h is the quadrupolar coupling constant and h is the asymmetry parameter. Angular frequency units are used and the e ects of relaxation and secondorder quadrupole are ignored.…”
Section: Theorymentioning
confidence: 99%